Towel curettage for a new definition of postpartum period after cesarean section - Elsharkawy, Suzan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: The objective of the present study was to compare effect of towel curettage as a new technique, to no curettage in caesarean section on postpartum period duration and hemoglobin level. Methods: Prospective, randomized controlled trial included 403 eligible participants that were attending Elshatby maternity hospital in the duration of this study (2016) and scheduled for primary caesarean section. The patients were randomized into two groups A and B. Group A had towel curettage after manual separation of the placenta, where the decidua and the placental bed were thoroughly curetted by a surgical towel. Group B had manual separation of placenta only. Results: Towel curettage actually shortens the puerperal bleeding days by almost a week and the volume of blood loss by around half a gram/dl, a situation that could be of great concern in the developing countries where iron deficiency anemia can be considered endemic. Conclusions: Suzan towel curettage is a new, simple, cheap methods that deceases duration of puerperium and the amount of useless blood loss post-partum, which may save a good percentage of women from suffering the negative influences of iron deficiency anemia.